IMPROVING PUBLIC HEALTH THROUGH INNOVATIVE AND COMMUNITY-BASED HEALTH PROMOTION STRATEGIES. - ABDUL HANAN (CV KULTURA DIGITAL MEDIA, 2024)
Public health is one of the key pillars of sustainable development. This article aims to explore innovative and community-based health promotion strategies to improve people's health status. Using a qualitative approach, this study identifies key challenges in health promotion and proposes evidence-based solutions. The results show that cross-sector collaboration, technology utilization, and community empowerment are key factors in improving the effectiveness of health promotion. This article provides practical recommendations for policy makers and implementers of public health programs.